Haploidentical hematopoietic stem cell transplantation using a reduced-intensity conditioning regimen which consist rituximab and mesencymal stem cell infusion in children; preliminary results - Atay, D.; Erbey, F.; Akcay, A.; Akbiyik, M.; Harman, O.; Ovali, E.; Ozturk, G. (NATURE PUBLISHING GROUP, 2015)
41st Annual Meeting of the European-Society-for-Blood-and-Marrow-Transplantation, Istanbul, TURKEY, MAR 22-25, 2015